Penguatan Nilai-Nilai Moderasi Beragama pada Santriwati Pondok Pesantren Mambaul Hisan Badalpandean Kecamatan Ngadiluwih - M Thoriqul Huda; Achmad Rifaldi; Muhammad Abdurahim; Moch. Faridho Alfaiq; Rizki Dwi Septian; Maula Shafira Putri Thohari; Alfina Nailul Muna (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
Islamic boarding school is an educational institution that focuses on teaching religious values ​​so that students who receive education at Islamic boarding schools will definitely be born with values ​​and norms that are in accordance with religious teachings. The aim of this research is to introduce the values ​​of religious moderation to female students at the Mambaul Hisan Islamic Boarding School, as well as how the practice of strengthening religious moderation values ​​is implemented directly by female students at the Mambaul Hisan Badalpandean Islamic Boarding School, Ngadiluwih District. The research method carried out by researchers is the PAR (Participatory Action Research) service method, which is a research method in which the researchers goes directly into the research field by collaborating with the boarding school, such as kyai, ustadzah and female students. This is to be an active part in planning implementing and evaluating program service. In this approach, information and knowledge can be exchanged and experiences shared between researchers and groups, so that the solutions obtained will be in line with local needs and values. The results of the research carried out were to find out how the practice of strengthening the values ​​of religious moderation was implemented directly by the female students of the Mambaul Hisan Badalpandean Islamic Boarding School, Ngadiluwih District.